A multifunctional plasmonic chip for bacteria capture, imaging, detection, and in situ elimination for wound therapy. Issue 11 (10th March 2020) - Gao, Xia; Wu, Haotian; Hao, Zhe; Ji, Xiangyi; Lin, Xiaodong; Wang, Shuo; Liu, Yaqing
Abstract : A multifunctional plasmonic gold chip is created to serve as a triple enhancer for PEF, SERS and NIR for bacteria analysis. Abstract : A multifunctional plasmonic gold chip has been constructed for early diagnosis and highly effective killing of bacteria, which is critical for human health. The chip features high bacterial capture efficiency, plasmon-enhanced fluorescence (PEF) and surface-enhanced Raman scattering (SERS) and can act as a highly sensitive sensor for dual-mode bacteria imaging and detection (down to 10 2 CFU mL −1 ) with good reliability and accuracy. The developed assay can distinguish Gram-positive S. aureus bacteria from Gram-negative E. coli bacteria, providing valuable information for therapy. Importantly, the chip presents excellent photothermal antibacterial activity (98%) and can inactivate both Gram-positive and Gram-negative bacteria in situ . Furthermore, the chip was used to effectively promote the wound healing process in bacteria infected mice in vivo, showing great potential for antibacterial applications.